2011
DOI: 10.3109/09638237.2011.577113
|View full text |Cite
|
Sign up to set email alerts
|

Mental health issues in fetal alcohol spectrum disorder

Abstract: Researchers are beginning to document the impacts of PAE on later mental health development. Further longitudinal study is needed to determine whether there is an increasing severity of mental health deficits and consequences with age, and whether any such changes reflect increasingly deteriorating environmental factors or brain-based factors. Additionally, research is needed to design interventions to better address the unique mental health needs of this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 39 publications
8
93
0
1
Order By: Relevance
“…This is consistent with the high rates of co-morbid psychiatric diagnoses among individuals with PAE (Pei et al, 2011), although surprising to see the low rate of reported anxiety concerns given the high rate of anxiety disorders reported for this population (Olson et al 2009). It is also noteworthy that it was the externalizing concerns, such as antisocial behavior and aggression that were described as the greatest concerns, as opposed to internalizing disorders.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is consistent with the high rates of co-morbid psychiatric diagnoses among individuals with PAE (Pei et al, 2011), although surprising to see the low rate of reported anxiety concerns given the high rate of anxiety disorders reported for this population (Olson et al 2009). It is also noteworthy that it was the externalizing concerns, such as antisocial behavior and aggression that were described as the greatest concerns, as opposed to internalizing disorders.…”
Section: Discussionsupporting
confidence: 77%
“…In Canada, the annual cost of supporting persons 0 to 53 years of age with FASD is estimated to be $5.3 billion (Stade et al, 2009). FASD, with mental health comorbidity rates as high as 90% with the most common being depression, mood and anxiety disorders, Attention Deficit Hyperactivity Disorder (ADHD), and Conduct Disorder (CD) (see Pei, Denys, Hughes, & Rasmussen, 2011 for a review). Moreover, these mental health issues appear to be lifelong spanning from childhood (O'Connor, 2001;O'Connor et al, 2002) to adolescence and adulthood (Barr et al, 2006;Spohr & Steinhausen, 1987;Steinhausen & Spohr, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Alcoholics have low folate levels, owing to reduced absorption, and following alcohol consumption, formic acid levels rise and can be neurotoxic. FASD is associated with significant neurological problems such as behavioural, cognitive, and motor impairment (Chokroborty-Hoque et al 2014) depression (Pei et al 2011), and epileptic seizures (Bell et al 2010;Nicita et al 2014). Women who consume alcohol during pregnancy may also have low folic acid and higher formic acid levels that can be teratogenic to the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with FASD have an increased susceptibility to mental health disorders, and this vulnerability persists across the lifespan [6,13]; over 90% of the FASD population is thought to experience comorbid mental health problems [48]. Most commonly, individuals with FASD experience depression and anxiety, attention-deficit hyperactivity disorder (ADHD), and conduct disorder (CD), but posttraumatic stress disorder, obsessive-compulsive disorder, oppositional defiance disorder, and bipolar disorder are also reported [48].…”
Section: Mental Health Needsmentioning
confidence: 99%
“…Most commonly, individuals with FASD experience depression and anxiety, attention-deficit hyperactivity disorder (ADHD), and conduct disorder (CD), but posttraumatic stress disorder, obsessive-compulsive disorder, oppositional defiance disorder, and bipolar disorder are also reported [48]. The nature of mental health issues in this population may change across the lifespan with alcohol and drug abuse being a serious concern for adults [48]. Compounding this risk is the fact that adults with FASD rarely access mental health services [49].…”
Section: Mental Health Needsmentioning
confidence: 99%